Penerapan Metode Pembelajaran Inkuiri Terbimbing dengan Mind Mapping untuk Meningkatkan Pemahaman Konsep Fisika Siswa - Kristiana Nathalia Wea; Rambu Ririnsia Harra Hau; Elisabeth Dua Kleruk (Jurnal Ilmiah Wahana Pendidikan, 2021)
Physics is a science that studies natural phenomena and their interactions, so that science skills are needed in its learning. These science skills can be developed using appropriate learning methods. This research was conducted to determine the application of the inquiry learning model with mind mapping to improve students' understanding of physics concepts. This research is an experimental research type of pre-experimental one group Pretest-Posttest. Data were taken using test and interview techniques. The results of this study indicate that learning using the inquiry method with mind mapping can improve students' understanding of physics concepts. Physical learning is not boring and fun because students are actively involved in the learning process.